Virtual professional development and informal learning via social networks - Dennen, Vanessa Paz; Myers, Jennifer B. 1980- (Premier reference source, 2012)
"This book will examine how individuals and organizations are using Web 2.0 tools to create informal learning and professional development opportunities" - Provided by publisher